Investigação do comportamento de ferramentas de aço-rápido no processo de rosqueamento interno em alta velocidade de corte - Mota, Paulo Rosa da (2006)
The main goal of this work is the evaluation of the performance of high-speed steel (HSS) taps when machining grey cast iron at high cutting speeds in dry conditions and when using MQL (minimal quantity of lubrication). The performance of four types of high speed steel with and without coating was investigated. They are: conventional HSS; HSS with addition of vanadium (HSS-E); HSS obtained by powder metallurgy (HSS-PM) and conventional HSS with surface treatment of nitriding. These tool materials are used in two coated situation: with TiN and multi layer TiN/TiNAl. It was used two tapping system, one using the collet tapping chuck of the machine tool without axial compensation, and the other using a self rotation system with axial compensation. The tool life criteria were based on dimensional tolerances of the threads, on tool wear and also on catastrophic failure of the tool. Analysis in the scanning electron microscope and optical microscope were done to measure the wear land and to determine the type and mechanisms of wear. The results showed that the effect of the cutting speed depends on the coating and the main wear mechanisms were adhesion and abrasion. The best performance was achieved with the multi layer coating TiN/TiNAl. The torque during the tapping operation was also monitored and the results for both system of fixation are compared. It was also performed a statistical investigation of the effects of some parameters. The cutting speed was the most influent parameter on tool wear. The application of cutting fluid improved the performance for all conditions tested.